Investigating Students’ Higher Order Thinking Skills (HOTS) in Writing Skill (A Case Study at the Eleventh Grade of a Senior High School in Banjar) - Pian Suci Sopiani; Iskhak Said; Ratnawati . (Universitas Bengkulu, 2019)
This study deals with the students’ Higher Order Thinking Skills (HOTS) in writing skill. This case study was aimed at figuring out the students use HOTS in writing, figuring out the kinds of the students’ HOTS in writing will be evident in writing, and figuring out the students’ responses on using HOTS in writing. The subject of this study was 21 students at the eleventh grade of a Senior High School in Banjar. Two research instruments used were the essay written test and the questionnaire. To assess the research instruments, the writer combined and synchronized the results by using triangulation analysis as adapted from Fraenkel et al. (2012, p. 559). The findings showed that Higher Order Thinking Skills (HOTS) were used by the students in learning writing. The findings also showed that the kinds of the students’ HOTS were evident that they improved their writing without any treatment. The findings also showed that there were some benefits of using HOTS in writing according to the students’ responses.